SOSIALISASI SAMPAH ORGANIK DAN NON ORGANIK SERTA PELATIHAN KREASI SAMPAH - Taufiq, Agus (AJIE (Asian Journal of Innovation and Entrepreneurship), 2015)
Dusun Klumprit II is a dusun that located in Wukirharjo, Prambanan, District Sleman, Province of Yogyakarta. Dusun Klumprit II is a prosperous dusun with the majority of livelihoods are in agricultural and livestock. The residents’ awareness and concern to manage the waste by the residents is still very low. The habit of burning the waste is still ingrained in the dusun to solve the waste problem. Besides, with burning the waste is considered as the fastest way to handle these problems. Not only that, there are some residents who throw their waste directly into the water bodies without thinking about the accumulation of the waste in the downstream water bodies and also pollution in water body as a result of the waste that they has thrown. It is feared that it will be imitated by the children of dusun as the successor of the dusun and also feared that the environmental carrying capacity will be weakened due to contamination that occurred. Such concerns can be reduced by growing the public awareness of the importance of removing and sorting the waste. The result of the program, the residents begin to understand the importance of managing the waste. Instead it will help to preserve the environment but it can also help the economy of the residents with the training of the creations that can be made from the waste. As well as the control approaches the waste to children through the activity of making crafts from the waste by their own efforts and hopes their creativity in the future can be honed to solve the waste problems and the cadres that cares into environments is born. With the procurement of the trash can, the residents can do the real actions in the management of waste by sorting both organic and non-organic.